Discounting of quantity surveying fees in South Africa - Claasen, Rudolph; Cumberlege, Roy (University of the Free State, 2014)
The discounting of professional fees has become a cause for concern among South African Quantity Surveying practitioners. These discounts are often 30% to 40% and, in some cases, substantially below the Tariff of Professional Fees published by the South African Council for the Quantity Surveying Profession (SACQSP). The firms which offer these excessively high discounts may be pricing their services well below their in-house operational costs which, with the quality of their professional services, eventually become unsustainable. A quantitative approach was used to conduct a research study to determine the effect of discounting of fees on the Quantity Surveying profession. The data was obtained by circulating a structured web-based questionnaire to registered professional Quantity Surveying firms in all nine provinces in South Africa. Results indicated that when Quantity Surveyors discount their fees, this impacts negatively on the quality of their professional services. Respondents further recommended that there should be some form of regulation regarding the discounting of fees, while others suggested that the current SACQSP recommended fee scale be replaced by the re-introduction of a statutory minimum fee scale which was applied prior to 1988. The findings arising from this research could support potential efforts by the SACQSP to resolve issues regarding this practice and serve to raise awareness among Quantity Surveying practitioners of the dangers inherent in, and resulting negative consequences of discounting their fees.

Afslag op professionele fooie het ‘n bron van kommer geraak onder die geledere van die Suid-Afrikaanse Bourekenkunde praktisyns. Hierdie afslag is soms tussen 30% en 40% en in sommige gevalle ver minder as die Tarief vir Professionele Fooie soos gepubliseer deur die Suid-Afrikaanse Raad vir die Bourekenaars Professie (SARBRP). Firmas wat hierdie buitensporige hoë afslag aanbied, mag moontlik hul direkte operasionele kostes onderprys, wat met die kwaliteit van hul dienste, uiteindelik onvolhoubaar raak. ‘n Kwantitatiewe benadering is gebruik vir hierdie navorsingstudie om die effek van afslag op fooie, op die Bourekenaars Professie te bepaal. Die data is verkry deur ‘n gestruktureerde web-gebaseerde vraelys aan geregistreerde professionele Bourekenaars in die nege provinsies van Suid Afrika te sirkuleer. Resultate het aangedui dat waar Bourekenaars afslag op fooie toestaan, dit ‘n negatiewe effek het op die kwaliteit van hul profesionele dienste. Respondente het verder aanbeveel dat daar ‘n vorm van regulering moet wees betreffende die toestaan van afslag op fooie en sommige het voorgestel dat die huidige SARBR-fooieskaal vervang moet word met die her-instelling van die statutêre minimum fooieskaal wat van toepassing was voor 1988. Die uitslae van die studie kan van hulp wees vir die SARBRP om oplossings te vind rakende kwelpunte rondom hierdie aspek asook om Bourekaars te waarsku van die gevare en die negatiewe uitwerkings, waar afslag op fooie toegestaan word.
Keywords: Discounting; Professional fees; Quantity surveying; Service quality